Modelling of organizational capabilities, innovation activities and performance of small and medium sized construction firms / Lee Yee Lin - Lee, Yee Lin (2015)
The relevance of innovation in service industries has been addressed within a project-based construction setting. Adopting innovative technologies and practices is important in accruing beneficial outcomes related to improved project delivery and performance as well as sustained competitive advantage of construction firms. However, little empirical emphasis has been paid to small and medium scale firms that constituted the bulk structure of the industry. The present study aims to develop an innovation framework, together with its mathematical equations, that considers organizational capabilities as a distinguishing character of superior firm performance in small and medium contracting firms (SMCFs). Construction innovation is defined as two different types of innovation activities, that is, technological and organizational innovations. Organizational capabilities involve several dimensions, such as entrepreneurship, organizational learning, integrated market orientation, human resource practice and inter-organizational network. The present study proposes an innovation framework, based on resource-based view (RBV) of firm, which assumes a positive effect of organizational capabilities on innovation, which in turns exerts a positive effect on firm performance. To date, to what extent these concepts are interrelated to each other and how innovation can be achieved within a small and medium (SME) setting remain unclear. Draw upon a mixed method, the proposed innovation framework and its mathematical equations are sequentially developed and validated with 157 empirical surveys and 12 in-depth interviews. Both the quantitative and qualitative studies are sampled on SMCFs (of general and specialist types) located in Kuala Lumpur, Malaysia. iv The purpose of the quantitative surveys was to gauge the strength of relationship between capabilities, innovation and firm performance. To this end, partial least square (PLS) approach of structural equation modelling (SEM) is utilized to produce quantitative results, which are then validated with a qualitative study that involves 12 experts specifically associated with SMCFs. The findings affirmed that capabilities can positively spur the effectuation of the two different, yet, complementing types of innovation desired by SMCFs. In turn, both the technological and organizational innovations are found to spur the development of superior performance of SMCFs. Further analysis indicated a partial mediating effect of the two distinct types of construction innovation. The results are expected to contribute to the academics in two main areas. First, the new innovation framework considers both capabilities-based antecedents and firm-based consequence to understand the nature of innovation in SMCFs. It provided an advanced explanation of how SMCFs innovate to accrue competent market position. Second, the conceptualization of innovation is consolidated on two different types of construction innovation, therefore advancing the understanding of innovation in SMCFs setting. Finally, the mathematical equations provide practical guidance for both practitioners and policymakers as to promote new value creation among SMCFs.